2013
DOI: 10.1097/mog.0b013e3283639326
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of pancreatic exocrine and endocrine secretion

Abstract: Purpose of review Recent advances in the regulation of pancreatic secretion by secretagogues, modulatory proteins and neural pathways are discussed. Recent findings Downstream events involved in secretagogue-stimulation of pancreatic secretion have been have been elucidated through characterization of the Src kinase pathway. An additional mechanism regulating vagus nerve effects on the pancreas involves Group II and III metabotropic glutamate receptors that are located presynaptically on certain vagal pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
0
32
0
3
Order By: Relevance
“…Although forced overexpression of the amyloidogenic mutant lysozymes leads to their rapid accumulation in the ER, it is estimated, in the case of human body, that the accumulation of the mutant proteins proceeds slowly, resulting in developing amyloidosis mainly in the 40-50's [5,45]. Several diseases including diabetes II [46] and amyotrophic lateral sclerosis (ALS) [47,48] are known to be brought about by the accumulation of misfolding proteins in the ER. A recent report indicated that, in Saccharomyces cerevisiae, unstable lysozymes may interact with a calnexin homolog, possibly causing their retention in the ER and subsequent elimination via ER-associated degradation [49].…”
Section: Grp78/bipmentioning
confidence: 99%
“…Although forced overexpression of the amyloidogenic mutant lysozymes leads to their rapid accumulation in the ER, it is estimated, in the case of human body, that the accumulation of the mutant proteins proceeds slowly, resulting in developing amyloidosis mainly in the 40-50's [5,45]. Several diseases including diabetes II [46] and amyotrophic lateral sclerosis (ALS) [47,48] are known to be brought about by the accumulation of misfolding proteins in the ER. A recent report indicated that, in Saccharomyces cerevisiae, unstable lysozymes may interact with a calnexin homolog, possibly causing their retention in the ER and subsequent elimination via ER-associated degradation [49].…”
Section: Grp78/bipmentioning
confidence: 99%
“…Exocrine secretion is tightly regulated by the autonomic nervous system in response to a meal and is mediated by numerous hormonal secretagogues and neurotransmitters [8, 9]. One of the most important mediators of exocrine secretion is cholecystokinin (CCK), secreted by I cells in the small intestine and by neurons in the brain [10].…”
Section: Normal Pancreatic Anatomy and Functionmentioning
confidence: 99%
“…CCK activates sensory afferent neurons in the duodenal mucosa, which in turn stimulates a vago-vagal reflex and the subsequent release of acetylcholine, ultimately leading to exocrine secretion by acinar cells. Exocrine secretory activity is complex and involves many different molecules and activating/inhibitory pathways that are outside of the focus of this review [7, 8, 11]. …”
Section: Normal Pancreatic Anatomy and Functionmentioning
confidence: 99%
“…These vesicles secrete insulin in proportion to the concentration of glucose in the blood [8]. Despite increased intracellular Ca 2 + being the primary insulin secretary signal, the cAMP signaling-dependent mechanism also plays an important role in augmenting glucose-stimulated insulin secretion (GSIS) [3,9].…”
Section: Introductionmentioning
confidence: 99%